Sens de l’expérience scolaire dans l’apprentissage des cadres juridiques de la formation professionnelle : l’exemple de la filière éducateur spécialisé - Cédric Laheyne (Recherches en Éducation)
Based on a study made by biographical interviews to identify different kinds of learning about right knowledges in special education work’s formation, this paper proposes to show the link between relation to knowledge and school socialisation and how, throught the streams baccalaureate, there is a advantage from initiated student into law studies. Then it brings to light the importance of social experience. This approach is particulary required to understand the motive for investment in specific subject, which has with few course hours.